Relativistic backward-wave oscillators of O-type with sheet electronic beams - A. V. Aksenchyk; I. F. Kirinovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
To generate high-power microwave oscillations it is proposed to use an O-type backward-wave oscillator (BWO) with an electrodynamic system on folded rectangular waveguides. The mathematical model uses sheet electron beams. The space charge is taken into account. Optimization calculations have been carried out and optimal generator efficiencies have been obtained for different sizes of electron beams, accelerating voltages 400–500 kV, currents 200–900 A. The analysis of interaction processes has been carried out. To increase the power of the generators proposed two-section scheme. Calculations showed, that the electronic efficiency of irregular relativistic BWO reaches 30–42 %, the output power is 50–170 MW.